Genetic obesity increases pancreatic expression of mitochondrial proteins which regulate cholesterol efflux in BRIN-BD11 insulinoma cells. Issue 3 (22nd March 2019) - Caridis, Anna-Maria; Lightbody, Richard J.; Tarlton, Jamie M.R.; Dolan, Sharron; Graham, Annette
Abstract : Pancreatic β-cells are sensitive to fluctuations in cholesterol content, which can damage the insulin secretion pathway, contributing to the aetiology of type 2 diabetes mellitus. Cholesterol efflux to (apo)lipoproteins, via ATP-binding cassette (ABC) transporter A1 (ABCA1), can prevent intracellular cholesterol accumulation; in some peripheral cells, ABCA1-dependent efflux is enhanced by promotion of cholesterol trafficking to, and generation of Liver X receptor (LXR) ligands by, mitochondrial sterol 27-hydroxylase (Cyp27A1 (cytochrome P450 27 A1/sterol 27-hydroxylase)) and its redox partners, adrenodoxin (ADX) and ADX reductase (ADXR). Despite this, the roles of mitochondrial cholesterol trafficking (steroidogenic acute regulatory protein [StAR] and 18-kDa translocator protein [TSPO]) and metabolising proteins in insulin-secreting cells remain wholly uncharacterised. Here, we demonstrate an increase in pancreatic expression of Cyp27A1, ADXR, TSPO and LXRα, but not ADX or StAR, in obese ( fa/fa ) rodents compared with lean ( Fa/? ) controls. Overexpression of Cyp27A1 alone in BRIN-BD11 cells increased INS2 expression, without affecting lipid metabolism; however, after exposure to low-density lipoprotein (LDL), cholesterol efflux to (apo)lipoprotein acceptors was enhanced in Cyp27A1-overexpressing cells. Co-transfection of Cyp27A1, ADX and ADXR, at a ratio approximating that in pancreatic tissue, stimulated cholesterol efflux to apolipoprotein A-I (apoA-I) in both basal and cholesterol-loaded cells; insulin release was stimulated equally by all acceptors in cholesterol-loaded cells. Thus, genetic obesity increases pancreatic expression of Cyp27A1, ADXR, TSPO and LXRα, while modulation of Cyp27A1 and its redox partners promotes cholesterol efflux from insulin-secreting cells to acceptor (apo)lipoproteins; this response may help guard against loss of insulin secretion caused by accumulation of excess intracellular cholesterol.